The impact of primary tumor site on outcomes of treatment with etoposide and cisplatin in grade 3 gastroenteropancreatic neuroendocrine carcinoma - Yoon, Sang Eun (J Cancer, 2019)
Background: Gastroenteropancreatic neuroendocrine carcinoma (GEP-NEC) is a heterogeneous disease in terms of embryonic origin, aggressiveness, prognosis, and genomic profiling. Data regarding the efficacy of etoposide and cisplatin (EP) as a standard treatment of the primary tumor site in GEP-NEC are limited. Materials and Methods: We analyzed 64 patients with histopathologically confirmed metastatic GEP-NEC who received EP at Samsung Medical Center, Seoul, Korea, between January 2010 and January 2018. Based on primary tumor site, outcome of treatment with EP was evaluated. Results: Primary sites included 22 foregut-derived GEP-NECs (stomach, n = 6; duodenum, n = 4; pancreas, n = 12), 4 midgut-derived GEP-NECs, 5 hindgut-derived GEP-NECs of the rectum, 25 GEP-NECs originating from the hepatobiliary (HB) tract, and 12 GEP-NECs involving only intra-abdominal lymph nodes. No patient had a complete response (CR) and 17 had a partial response (PR), resulting in a 27.9% response rate (RR). When evaluating the efficacy of EP based on primary tumor site, the RR was most favorable in GEP-NECs involving only intra-abdominal lymph nodes, followed by GEP-NECs originating from foregut, midgut, HB, and hindgut. However, no statistically significant difference was observed for RR based on primary tumor site (P = 0.821). Similarly, no significant differences were found for progression-free survival (PFS) among patients with GEP-NECs arising from various primary tumor sites. Conclusion: Results from this study showed that RR and PFS associated with EP treatment were not different based on the primary tumor site in patients with advanced or metastatic GEP-NEC.